2023
DOI: 10.1021/acs.chemrev.3c00215
|View full text |Cite
|
Sign up to set email alerts
|

Non-Native Site-Selective Enzyme Catalysis

Dibyendu Mondal,
Harrison M. Snodgrass,
Christian A. Gomez
et al.

Abstract: The ability to site-selectively modify equivalent functional groups in a molecule has the potential to streamline syntheses and increase product yields by lowering step counts. Enzymes catalyze site-selective transformations throughout primary and secondary metabolism, but leveraging this capability for non-native substrates and reactions requires a detailed understanding of the potential and limitations of enzyme catalysis and how these bounds can be extended by protein engineering. In this review, we discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 471 publications
(843 reference statements)
0
6
0
Order By: Relevance
“…Direct hydroxylation of CBA and BCPA cores provides difunctionalized templates from which selective transformations of either the protected amine or the free alcohol functionality can lead rapidly to diverse small-molecule collections . As summarized in Scheme , the newly introduced hydroxyl group in (1 S ,2 S )- 14 is compatible with removal of the Boc group and N-acylation to give, in this case, a substrate 30 for potential elaboration by cross-coupling chemistry.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Direct hydroxylation of CBA and BCPA cores provides difunctionalized templates from which selective transformations of either the protected amine or the free alcohol functionality can lead rapidly to diverse small-molecule collections . As summarized in Scheme , the newly introduced hydroxyl group in (1 S ,2 S )- 14 is compatible with removal of the Boc group and N-acylation to give, in this case, a substrate 30 for potential elaboration by cross-coupling chemistry.…”
Section: Results and Discussionmentioning
confidence: 99%
“…48 No changes in selectivity were observed during our substrate scope evolution, 39 indicating that either such changes were not occurring or our UPLC assays could not detect them. More broadly, efforts to alter the site selectivity of enzymatic C-H functionalization were rare at the time we initiated our efforts, 6,9 and the successful examples in the literature did not involve direct screens for altered selectivity 50 .…”
Section: Early Fdh Engineering Effortsmentioning
confidence: 99%
“…General and rapid means to tune binding so that different substrates and sites/functional groups on those substrates can react selectively must be developed. 9 When I started my independent research group, several features of flavin dependent halogenases (FDHs) suggested that they could be amenable to these requirements (Figure 1C). [10][11][12][13] The tryptophan halogenases PyrH, 14 Thal, 15 and PrnA 16 were known to selectively halogenate tryptophan at its 5-, 6-, or 7-position, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…46–49 In contrast to small molecule catalysts, enzymes can be continuously optimized, redesigned and repurposed for performing specific C–H reactions with industrial importance. 50–52 Residues in the Second Coordination Sphere (SCS) and Remote Areas (RA) became increasingly important tools for modulating and improving enzyme activity and product selectivity. 53–59…”
Section: Introductionmentioning
confidence: 99%